Minority Salience and Political Extremism - Tommaso Colussi; Ingo E. Isphording; Nico Pestel (Institute of Labor Economics (IZA), 2016)
This paper studies electoral effects of exposure to religious minorities in the context of Muslim communities in Germany. Using unique data on mosques' construction and election results across municipalities over the period 1980-2013, we find that the presence of a mosque increases political extremism. To establish causality, we exploit arguably exogenous variation in the distance of the election date to the month of Ramadan, when Muslim communities become more visible to the general public. Our findings show that vote shares for both right- and left-wing extremist parties become larger when the election date is closer to Ramadan. We additionally show that the change in minority salience also increases the likelihood of politically motivated crimes against Muslims.
Keywords: D72; D74; J15; 330; minority salience; Muslims; voting; conflict